Experiencing Citizenship: How Immersive Pedagogies Transform Student Interest and Academic Achievement in Pancasila Education - Neliana Neliana; Mulyadi Mulyadi; Badaruddin Kaddas (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Civic education in the twenty-first century faces substantial pedagogical challenges, particularly the dominance of teacher-centered instruction that constrains active student participation. In Indonesia, Pancasila Education is frequently delivered through conventional lecture-based methods, resulting in diminished learning motivation and suboptimal academic achievement among elementary school students. This empirical study examines the effect of combining Role-Playing and Experimental methods on the learning interest and academic outcomes of sixth-grade students at Elementary School 239 Inpres Nipa, Maros Regency, Indonesia. Employing a quantitative pre-experimental design with a One-Group Pretest-Posttest format, the research involved 20 sixth-grade students recruited through total (saturated) sampling. Data were collected via cognitive achievement tests, a Likert-scale learning interest questionnaire, structured observation sheets, and documentary records. The gathered data were analyzed descriptively and through analysis-of-variance (ANOVA) procedures using SPSS version 26. Findings revealed significant improvements post-intervention: the mean student learning outcome score rose from 45.00 to 82.50, while the mean learning interest score increased from 49.80 to 81.13. ANOVA results confirmed a highly statistically significant main effect (F = 309.932, p = 0.000 < 0.05). The integrated application of Role-Playing and Experimental methods fosters an interactive, experiential learning environment that strengthens students' deep comprehension of Pancasila values and active engagement in civic education. Ultimately, these methods constitute a viable instructional alternative for supporting the implementation of the Merdeka Curriculum in primary elementary schools.